Найдите значение выражения. (\sqrt{2}-2\sqrt{3})^{2} + 4\sqrt{6}


Найдите значение выражения.

Sayva11 Sayva11    1   15.04.2021 18:55    0

Ответы
150819761 150819761  15.05.2021 18:55

14

Объяснение:

(\sqrt{2}-2\sqrt{3} )^{2} +4\sqrt{6} = (\sqrt{2} )^{2} -4\sqrt{2} \sqrt{3} +4(\sqrt{3} )^{2} + 4\sqrt{6} =2 -4\sqrt{2} \sqrt{3}+ 4(\sqrt{3} )^{2} + 4\sqrt{6} = 2 - 4\sqrt{6} + 4(\sqrt{3} )^{2} +4\sqrt{6} = 2 - 4\sqrt{6} + 4*3 +4\sqrt{6} = 2 - 4\sqrt{6} + 12 +4\sqrt{6} = 14 - 4\sqrt{6} + 4\sqrt{6} = 14

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра